Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1136/bjophthalmol-2016-309104
|View full text |Cite
|
Sign up to set email alerts
|

Image artefacts in swept-source optical coherence tomography angiography

Abstract: Image artefacts occur frequently in OCTA images. The artefacts are more frequent in eyes with pathology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
134
2
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 160 publications
(145 citation statements)
references
References 10 publications
0
134
2
6
Order By: Relevance
“…These include, but are not limited to, projection, segmentation, motion, masking, unmasking and blink artefacts 3 4. Spaide et al 3 speculated that in OCTA, the calibre of vessels may be depicted to be larger than in their real state, but vessels calibres were not specifically quantified in order to validate this hypothesis.…”
Section: Introductionmentioning
confidence: 99%
“…These include, but are not limited to, projection, segmentation, motion, masking, unmasking and blink artefacts 3 4. Spaide et al 3 speculated that in OCTA, the calibre of vessels may be depicted to be larger than in their real state, but vessels calibres were not specifically quantified in order to validate this hypothesis.…”
Section: Introductionmentioning
confidence: 99%
“…This can produce artifacts, but allows for a more robust visualization of vasculature [26]. The exact localization and thickness of the CC slab vary between 0 and 34 µm below the RPE/Bruch's membrane reference and between 4.4 and 30 µm, respectively, depending on the device used [17,20,27,28]. Notably, manufacturers use various definitions of the CC slab level, and not all of them offer a presetting for CC examination yet (Table 1).…”
Section: Heidelberg Spectralismentioning
confidence: 99%
“…(2) Segmentation errors in OCTA are frequent in the presence of retinal pathologies and can affect all layers, including the CC [20]. Notably, en face imaging requires an accurate segmentation of retinal layers, which can be reliably achieved in normal maculae.…”
Section: Heidelberg Spectralismentioning
confidence: 99%
“…In recent studies, at least one form of artifact was identified in 73–89.4% of OCTA images with more prevalence in eyes with ocular pathology and poor visual acuity 33, 45. The artifacts were severe enough to preclude accurate grading of the images in 17.6% 41 . In addition, correction of artifacts such as segmentation artifact can be challenging.…”
mentioning
confidence: 99%